(untitled) (LEARNing Landscapes, 2009)
From the earliest age, children begin to practice their imaginary characters, their separate visions of strength and weakness, of love and loss. By the time they enter kindergarten they are ready to build complex social and literary worlds in which friendship, fantasy, and fairness—the Three F’s—are inalienable rights, and every child tries to find a secure place in an intimate community. A preschool or kindergarten without a substantial playtime puts everyone at a disadvantage, for play is the primary reality for its members. Within the familiar process of inventing new characters and plots, children continue to develop the intuitive language that binds us together in a functioning social entity. This is the true early literacy.